Teaching Strategies and its Influence on Students’ English Writing Skills at Secondary School Certificate - Qudsia Fatima, (PJE, 2023)
Teaching strategies perform a great role in students’ learning at every level of education. This paper presents achievement in English writing skills and the practices of teaching used by teachers. Under Mixed-method, Sequential exploratory design was chosen for this study.